Transvaginal Extraction of Laparoscopic Right Hemicolectomy Specimen - Gonzalo Martin; Mohammed Iyoob Mohammed Ilyas; José F Noguera; Valentine Nfonsam (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
Natural Orifice Specimen Extraction (NOSE) maintains the benefits of minimally invasive surgery obviating the need to extend the port site incisions for specimen extraction. We describe the technique of transvaginal extraction of a laparoscopic right hemicolectomy specimen in sexually active 63 year old female. This included intracorporeal ileo-colic anastomosis and transvaginal colpotomy and extraction of specimen. Periodical follow up for 6 months did not show any complications with no reported dyspareunia. Multiple smaller studies have confirmed the safety of transvaginal extraction of resected colon. Transvaginal extraction of colonic specimen is an attractive option in women with minimal side effects if any.